A Novel Research on Anti- Diabetic Syrup Using Plants Seeds Abelmoschus Esculents and Punica Granatum - Saxena, Chitransh; Sharma, Manmohan; Sharma, Hariom; Sharma, Anil; Vyas, Girish (Asian Journal of Pharmaceutical Research and Development, 2023)
Abelmoschus Esculents plant is a vegetable and itsgeneral name is lady finger is most of the famous vegetable in India and other countries because of all the medical advantages it has. And Punica Granatum is also known as pomegranate this name is commonly used in India.This is a fruit also large scale of production in country. They both have (lady finger and Pomegranate) an excellent source of Nutrition and control the human blood sugar level. The focus of this review is on Abelmoschus esculents (okra) and pomegranates as anti-oxidants, agents for reducing tiredness, and most importantly, diabetes therapeutics. Pomegranate and lady finger (also known as okra) fibres and minerals have also long been recognised as sources of energy and biotherapeutics from which essential medications can be manufactured. The analysis examines how well okra and pomegranates can transform the majority of medications used to treat various disorders. Additionally, it expresses hope that pomegranate and okra would succeed in the various stages of clinical testing.